1998
DOI: 10.1063/1.368302
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hot-carrier induced interface state density in polycrystalline silicon thin-film transistors

Abstract: Polysilicon thin-film transistors are of great interest for their application in large area microelectronics and especially for their circuit applications. A successful circuit design requires a proper understanding of the electrical characteristics and in the present work some specific aspects related to the hot-carrier induced electrical instabilities are presented. In particular, generation of interface states near the drain junction occurs when the devices are operated for a prolonged time in the so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In Fig. 4(a), are shown the transfer characteristics measured in a p-channel TFT before and for different times during bias-stress performed at V g (stress) À V t = À4 V and V ds = À14 V. As can be seen an appreciable transconductance degradation occurs due to hot carrier effects and has been attributed to the formation of interface states at semiconductor-insulator interface close to the drain junction where the electric field is maximum [7]. Let us now discuss the behavior of the output characteristics of p-channel TFT after bias-stressing.…”
Section: Electrical Stabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…In Fig. 4(a), are shown the transfer characteristics measured in a p-channel TFT before and for different times during bias-stress performed at V g (stress) À V t = À4 V and V ds = À14 V. As can be seen an appreciable transconductance degradation occurs due to hot carrier effects and has been attributed to the formation of interface states at semiconductor-insulator interface close to the drain junction where the electric field is maximum [7]. Let us now discuss the behavior of the output characteristics of p-channel TFT after bias-stressing.…”
Section: Electrical Stabilitymentioning
confidence: 96%
“…These effects are induced by the presence of intense electric fields at the drain junction, determined mainly by the abruptness of the lateral doping profile. Extensive investigation of HCE in polysilicon TFTs has shown that, similarly to c-Si MOSFETs, the device degradation is controlled by the formation of interface states and oxide traps and charge injection in the gate oxide [7,8]. Recently, it has been also proposed that hot carrier induced defects could be generated at the grain boundaries creating a damage region close to the drain junction [8].…”
Section: Introductionmentioning
confidence: 98%
“…Kink-effect and hot carrier instabilities are related to impact ionization at the drain junction induced by the presence of intense electric fields at the drain junction, determined mainly by the abruptness of the lateral doping profile. In particular, it has been shown [4,5] that in polysilicon TFTs, similarly to c-Si MOSFETs, the device degradation is controlled by the formation of interface states, oxide traps and charge injected in the gate oxide. It has been also proposed that hot carrier-induced defects could be generated at the grain boundaries, creating a damaged region close to the drain junction [5].…”
Section: Introductionmentioning
confidence: 99%
“…As the channel length is becoming shorter, device reliability of LTPS-TFT's must be taken into account [7,8].…”
Section: Introductionmentioning
confidence: 99%